Przestępstwo bójki i pobicia w świetle statystyki sądowej w Wielkopolsce w latach 1976 -1984 - Gosieniecki, Piotr (Wydział Prawa i Administracji UAM, 1986)
The study of the size and extent of delinquency belongs to the group of basic criminological problems. The article attempts to present the dimensions of sentencing for the participation in a fight and a battery (art. 158., 159 of the Penal Code) in 5 provinces of Wielkopolska. It contains a detailed discussion on the share of sentences for the above offences among general number of sentences for offences against life and health. The analysis of the extent and dynamics of that phenomenon together with the comparison of the intensity of sentencing have been performed. The trends in delinquency (art. 158, 159 of the Penal Code) in urban and rural areas and othe comparison of the degree of the intensity of delinquency according to the place of committing an offence (town-village) have been presented. The article contains also the analysis of 3 basic characteristics of offenders, i.e. their sex, age and previous records. The method of exposing the data and their analysis aim at determining the similarities and differences with respect to the discussed phenomenon in 5 provinces of Wielkopolska.
The Offences of Fight and Battery in the Light af Cour Statistics in Wielkopolska in 1976-1984